SOME ASPECTS OF USING GOOGLE APPS INTO HIGHER EDUCATIONAL INSTITUTION (Journal of Information Technologies in Education (ITE), 2014)
The article investigated the concept of information and educational space» and determined the aspects of integration of its services. The unified authentication is an important component of information and educational space. It can be based on LDAP-directory. This study presented the main advantages of using Google Apps in process of learning. We described the experience of the integration Google Apps into information and educational space of Department of Physics and Mathematics of Ternopil V. Hnatyuk National Pedagogical University
Keywords: information and educational space; unified authentication; Google Apps; LDAP